Knowledge, Skills and Work Attitude as Correlates to Job Performance in Exploratory Adtech Program of Grade 8 Students - Bisenio, Richard; Bajet, Nelson (JPAIR Multidisciplinary Research, 2015)
The enhanced K-12 Basic Education Program seeks to provide a quality 12-year basic education program that each Filipino is entitled and in consistent with Article XIV, Section 2 (I) of the Philippine Constitution which states that the state shall establish, maintain, and support a complete adequate, and integrated system of education relevant to the needs of the people and society.The study aimed to determine the level of performance of the Grade 8 Adtech students of the Philippine Science High School Ilocos Region Campus, San Ildefonso, Ilocos Sur in S.Y. 2013-2014. The study made use of descriptive correlational research design. Results showed that the overall grade exhibited a "very good" level of performance in the curricular subjects. Knowledge test of the student obtained an "Excellent" grade, and students’ work attitude is highly important. The student performance along knowledge (0.284), skills (0.301); attitude (0.272) in the Exploratory AdTech Program resulted that no significant relationship. The correlation coefficients between the level of performance of the students in Exploratory AdTech Program and the students’ performance along attitudes, manifested a significant relationship. Matching of competency requirements and standards of the 12-year basic education are necessary to acquire skills and match the College Readiness Standards for further education and future employment of students.